2000
DOI: 10.1046/j.1523-536x.2000.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth and the Development of Acute Trauma Symptoms: Incidence and Contributing Factors

Abstract: Posttraumatic stress disorder after childbirth is a poorly recognized phenomenon. Women who experienced both a high level of obstetric intervention and dissatisfaction with their intrapartum care were more likely to develop trauma symptoms than women who received a high level of obstetric intervention or women who perceived their care to be inadequate. These findings should prompt a serious review of intrusive obstetric intervention during labor and delivery, and the care provided to birthing women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
425
4
31

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(502 citation statements)
references
References 25 publications
25
425
4
31
Order By: Relevance
“…Lack of supportive care is also associated with postnatal PTSD (Soet, Brack, & Dilorio, 2003;Creedy et al, 2000;Czarnocka & Slade, 2000;Wijma, Soderquist, & Wijma, 1997). A pertinent issue here is that positive support and lack of support are likely to have different effects.…”
Section: Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of supportive care is also associated with postnatal PTSD (Soet, Brack, & Dilorio, 2003;Creedy et al, 2000;Czarnocka & Slade, 2000;Wijma, Soderquist, & Wijma, 1997). A pertinent issue here is that positive support and lack of support are likely to have different effects.…”
Section: Ptsdmentioning
confidence: 99%
“…On the one hand, there is evidence that women who suffer extreme complications, such as stillbirth or life threatening events, during pregnancy and labour are at greater risk of developing PTSD. Research also suggests that assisted delivery or emergency caesarean section can increase risk of PTSD (Ayers, Harris, Sawyer, Parfitt, & Ford, 2009;Creedy, Schochet, & Horsfall, 2000;Maclean, McDermott, & May, 2000;Soderquist, Wijma, & Wijma, 2002). On the other hand, studies that examine the relative importance of obstetric and subjective experiences clearly show subjective experience is more important in postnatal PTSD.…”
Section: Ptsdmentioning
confidence: 99%
“…Moreover, infants typically exhibit a developmental trend from a preference for looking which results in clinical symptoms of PTSD (Creedy, Shochet & Horsfall, 2000;Czarnocka & Slade, 2000). Moreover, the mother-infant relationship is affected by maternal symptoms of PTSD (Davies, Slade, Wright & Stewart, 2008;McDonald, Slade, Spiby & Iles, 2011) and PND (Edhborg, Lundh, Seimyr & Widstorm, 2001;Murray, 1992;Murray, Fiori-Cowley, Hooper & Cooper, 1996;Taylor, Atkins, Kumar, Adams & Glover, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention during labour and delivery, particularly assisted vaginal delivery or emergency caesarean section, are related to appraisal of birth as traumatic (Ayers, 1999;Soet et al, 2003) and symptoms of PTSD in some studies (Creedy, Shochet, & Horsfall, 2000;MacLean, McDermott, & May, 2000;Soderquist et al, 2002). However, other studies find no influence of type of delivery on subjective distress (Skari, Skreden, Malt et al, 2002) or PTSD symptoms (Ayers, 1999;Czarnocka & Slade, 2000).…”
mentioning
confidence: 99%
“…A review found that variables such as personal expectations, the amount of support from caregivers, the quality of the caregiver-patient relationship, and involvement in decision making were more important than the birth environment, pain, immobility, medical interventions, and continuity of care in determining women's evaluations of their birth experience (Hodnett, 2002). Limited evidence suggests support during birth is associated with less anxiety and depression in the postnatal period (Scott et al, 1999); and a perceived lack of support from healthcare professionals during birth has been associated with symptoms of PTSD following birth (Creedy et al, 2000;Czarnocka & Slade, 2000). These findings suggest that support from caregivers during birth may have a strong affect on women's emotional, anxiety and trauma reactions following childbirth.…”
mentioning
confidence: 99%